Is plasma GABA level a biomarker of Post-Traumatic Stress Disorder (PTSD) severity? A preliminary study. (30th July 2016) - Trousselard, Marion; Lefebvre, Bertrand; Caillet, Lionel; Andruetan, Yann; de Montleau, Franck; Denis, Josiane; Canini, Frédéric
Abstract: Objectives: An increased reactivity to the environment is observed in Post-Traumatic Stress Disorder (PTSD). It would be related to impairment of the Gamma Amino Butyric Acid (GABA) neurotransmission. The study aimed to evaluate plasma GABA concentration as a candidate for PTSD severity biomarker. Methods: This hypothesis was studied in 17 PTSD patients and 17 healthy Controls using classic and emotional Stroop paradigms. Plasma GABA concentrations were assessed before and after both Stroop tests to evaluate GABA basal tone and GABA reactivity (change in GABAp), respectively. Results: During baseline, PTSD had lower plasma GABA concentrations than the Controls. After the Stroop conflicts GABA reactivity was also lower in PTSD than in the Controls. The GABA baseline tone was negatively correlated with the severity of the PTSD symptoms. This relation was only marginally observed for GABA reactivity. The results produced a trend due to the small size of the sample compared to the number of statistical results given. Conclusion: Altogether, the reduced GABA concentration observed in PTSD could be considered as a possible biomarker for PTSD severity. Highlights: Although the diagnosis and follow-up for PTSD are currently based on a set of symptoms and/or psychometrics assessments, it lacks pertinent biomarkers for PTSD traits (risk factor or risk marker), disease state, or disease rate. This paper evaluated GABA impairment in Post-Traumatic Stress Disorder (PTSD) using plasma GABA concentration. GABAp might be a candidate, either detected in the brain or in the blood. This study suggests that the GABAp level would be a good candidate for the follow-up of the severity of stress-induced pathologies.